Scoping Review of the Occupational Health and Safety Governance in Sudan: The Story So Far - Rasha A. Abdelrahim; Victor O. Otitolaiye; Faris Omer; Zeena Abdelbasit (Elsevier, 2023)
Background: The reoccurrence of occupational accidents in Sudan is evidence of a lack of effective Occupational Health and Safety (OSH) governance in Sudan. Methods: This scope review research articles on OSH governance in Sudan from different sources, including international websites, official government websites, original research articles in journals, and various reports. The five stages of the scoping review followed in this study are: identifying the research question; identifying relevant studies; study selection; charting the data; collating, summarizing, and reporting the results. Results: There is numerous legislation in place; however, there is no evidence of their enforcement, and no formal bodies at the national level are identified as being responsible for their enforcement. Conclusion: Having multiple authorities with overlapping responsibilities hinders OSH governance. An integrated governance model is proposed to eliminate overlapping duties and to facilitate the participation of all stakeholders in the governance process.